2018
DOI: 10.11604/pamj.2018.30.122.14820
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ knowledge of ultrasonography: effects of a simulation-based ultrasound training program

Abstract: IntroductionThe use of simulation devices in medical education is becoming more prevalent with each passing day. The present study aimed to teach medical students to perform ultrasonography via a simulation-based ultrasound training program.MethodsThe study was prospectively conducted on final year medical students who had not received previous ultrasound training and who came to the Emergency Department of the Kirikkale University Faculty of Medicine between July 2015 and July 2016. Ultrasound training was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The effectiveness of a short course utilized in this study is in accordance with findings from a previous study, wherein short simulation-based training programs were found to be adequate for medical students to learn how to perform ultrasonography. [ 17 ] Future studies in Saudi Arabia can be conducted using a comprehensive US curriculum using the peer-teaching concept[ 18 ] or through a comprehensive 2-week program for final year medical students that incorporates hands-on US experience with live patients proctored by radiologists. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of a short course utilized in this study is in accordance with findings from a previous study, wherein short simulation-based training programs were found to be adequate for medical students to learn how to perform ultrasonography. [ 17 ] Future studies in Saudi Arabia can be conducted using a comprehensive US curriculum using the peer-teaching concept[ 18 ] or through a comprehensive 2-week program for final year medical students that incorporates hands-on US experience with live patients proctored by radiologists. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…The main criticism rests on the scarcity of scientific studies analyzing the real impact of simulation-based ultrasound training on clinical practice. Indeed, the majority of available studies either analyze the effect of simulator training on the simulation experience [ 21 , 22 ] or use subjective evaluations to support their conclusions [ 23 - 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A randomized study also demonstrated that using a simulator to facilitate the acquisition of skills in cardiac ultrasound in addition to conventional educational approaches was feasible and useful, with improved examination scores, shortened examination times, and improved student satisfaction [ 99 ]. Simulation-based ultrasound training programs using other kinds of high-fidelity simulators were found to be useful for helping medical students train in cardiac ultrasound and other applications of POCUS [ 100 , 101 ]. Ultrasound simulators can also be useful self-directed tools that help previously trained students retain and improve their scanning skills [ 102 ].…”
Section: Technological Advances In Educational Toolsmentioning
confidence: 99%